PERAN POLA ASUH ORANG TUA DALAM MEMBENTUK PERILAKU SOSIAL ANAK USIA DINI DI TK NURUL ISLAM - Raodah Raodah (STAI Al Mujtama Pamekasan, 2026)
Social behavior in early childhood is strongly influenced by the family environment, particularly the parenting styles applied by parents. Inappropriate parenting patterns may affect the development of childrens social behavior in the school environment. Therefore, this study discusses the role of parental parenting in shaping the social behavior of early childhood at TK Nurul Islam. The purpose of this study was to examine the role of parenting styles in shaping early childhood social behavior and to identify the impact of parenting practices on childrens social behavior at school. This study employed a qualitative research method, with data collected through observations and interviews with classroom teachers and parents of children at TK Nurul Islam. The results of the study indicate that parenting styles play an important role in shaping childrens social behavior. The findings show that the dominant parenting style applied by parents tends to be authoritarian, which affects childrens social behavior, such as difficulties in cooperating with peers, emotional instability, and limited ability to manage emotions appropriately.